Surface texturing and combinatorial approaches to improve biocompatibility of implanted biomaterials - Xu, Li-Chong; Siedlecki, Christopher A. (Frontiers in Physics, 2022)
Biomaterial associated microbial infection and blood thrombosis are two of the barriers that inhibit the successful use of implantable medical devices in modern healthcare. Modification of surface topography is a promising approach to combat microbial infection and thrombosis without altering bulk material properties necessary for device function and without contributing to bacterial antibiotic resistance. Similarly, the use of other antimicrobial techniques such as grafting poly(ethylene glycol) (PEG) and nitric oxide (NO) release also improve the biocompatibility of biomaterials. In this review, we discuss the development of surface texturing techniques utilizing ordered submicron-size pillars for controlling bacterial adhesion and biofilm formation, and we present combinatorial approaches utilizing surface texturing in combination with poly(ethylene glycol) (PEG) grafting and NO release to improve the biocompatibility of biomaterials. The manuscript also discusses efforts towards understanding the molecular mechanisms of bacterial adhesion responses to the surface texturing and NO releasing biomaterials, focusing on experimental aspects of the approach.